2003
DOI: 10.1110/ps.0372903
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the stability of partly folded proteins using TMAO

Abstract: Standard methods for measuring free energy of protein unfolding by chemical denaturation require complete folding at low concentrations of denaturant so that a native baseline can be observed. Alternatively, proteins that are completely unfolded in the absence of denaturant can be folded by addition of the osmolyte trimethylamine N-oxide (TMAO), and the unfolding free energy can then be calculated through analysis of the refolding transition. However, neither chemical denaturation nor osmolyte-induced refoldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 38 publications
8
152
0
Order By: Relevance
“…This stabilization happens without changing the baselines of the unfolding curve or the m-value for the process (22). TMAO can therefore be used in stability measurements of proteins that unfold at low denaturant concentrations (23). The urea denaturation curves at 0, 0.5, and 1.0 M TMAO were therefore analyzed globally assuming that the pre-and posttransition baselines and the m-values are the same at all TMAO concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…This stabilization happens without changing the baselines of the unfolding curve or the m-value for the process (22). TMAO can therefore be used in stability measurements of proteins that unfold at low denaturant concentrations (23). The urea denaturation curves at 0, 0.5, and 1.0 M TMAO were therefore analyzed globally assuming that the pre-and posttransition baselines and the m-values are the same at all TMAO concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The proteins used in this study were drawn from those reported in studies by Myers et al and Hong et al, along with some we added (7,(29)(30)(31)(32)(33)(34)(35). The m values depend on salt concentration and pH, so only those proteins are included that are monomeric, denature reversibly in the presence of urea at neutral pH and moderate salt, exhibit two-state behavior, and contain no cofactor or metal ion.…”
Section: Discussionmentioning
confidence: 99%
“…Current experimental evidence points to hydrogen bonding. Specifically, at least four natively unfolded proteins can be forced to fold upon addition of organic osmolytes (87,120,121). In such cases, the total free energy of osmolyteinduced folding can be dissected into individual group transfer-free energies (86), whereupon it becomes evident that the peptide backbone is the dominant contributor.…”
Section: Part 7 Protein Folding: Analog Mechanism Vs Digital Mechanismmentioning
confidence: 99%